Self-excitation starting system and self-excitation starting method for static synchronous series compensator - SONG JIEYING; SONG FANGFANG; LU ZHENGANG; WEI ZHIYONG; YU JIANCHENG; ZHAO GUOLIANG; CAI LINHAI; LIU YUN; HUO XIANXU (2017)
The invention relates to a self-excitation starting system and a self-excitation starting method for a static synchronous series compensator. The system comprises a first circuit breaker which is mounted on an alternating-current bus of an external alternating-current system, a winding on one side of a transformer is parallelly connected to two sides of the first circuit breaker through an alternating-current side switch, and a winding on the other side of the transformer is parallelly connected to two sides of a bypass thyristor. The bypass thyristor is parallelly connected to two sides of a second circuit breaker which is connected with a filter, and the filter is connected with a series converter which is connected with a controller. According to the technical scheme, a cascaded H-Bridge multi-level structure based SSSC (static synchronous series compensator) system mathematic model is derived, single-phase phase-locked loops and novel two-stage direct-current voltage stabilizing strategies are designed, a